Physical activity and health in europe. - Cavill, Nick; Kahlmeier, Sonja; Racioppi, Francesca (World Health Organization, 2006)
This booklet is written for European policy-makers and leaders from different sectors that can promote physical activity, including health, sports and recreation, transport, employment, urban planning, education and the mass media. It sets out the facts about health-enhancing physical activity, provides examples of action already being taken, highlights the contributions that can be made by health and other sectors and makes the case for concerted action across the WHO European Region.